(un)Learning Curves: Stripping the Myth of the ‘Real’ Woman - Ramírez, Kimberly (Latin American Theatre Review, 2017)
This essay considers how commonly held stereotypes associated with Latina bodies influence student readings of scripts that exploit, perpetuate, or interrogate the myth that “real women have curves.” Learned impulses to become visible or to classify the Other introduce strong anxieties of leaving the Latina body unmarked, but championing curves as “real” interprets excess as visibility, costuming Latinas in consumable flesh while thinner, less curvaceous bodies appear culturally compromised, disregarded, or disembodied. That curves make a woman “real” promotes an imagined, intermediate body that becomes easily marked between two binaries: spectrums of Latina bodies become singular, situated, and simplified, (mis)perceived as not black or white but brown, not fat nor thin but curvy. Playwrights, performers, and professors must collectively shift the Latina body learning curve(s) by un-learning the pseudo-feminist “real women have curves” myth with impressionable college students.